2023
DOI: 10.1037/fam0001040
|View full text |Cite
|
Sign up to set email alerts
|

Indirect associations between infant sleep, parental sleep, and sexual well-being in new parent couples.

Abstract: New parents’ sexual frequency and desire fluctuate throughout the transition to parenthood (i.e., the first year after childbirth). Poorer infant sleep and parental sleep are each associated with lower sexual frequency and desire in cross-sectional research. According to the theory, infant sleep might shape new parents’ sexual frequency and desire in so far as it disrupts parental sleep, though this pathway has yet to be examined. We examined the role of parental sleep in the indirect pathway between infant sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…MacKenzie conducted a study in 203 mothers assessing the correlations of infant sleep quality, parents' sleep, frequency of intercourse and sexual desire up to 12 months after delivery. It was found that poorer infant sleep was associated with poorer partner sleep quality, translating into a lower frequency of intercourse and lower sexual desire [85]. Rowland also showed that insufficient sleep weakened women's libido during the postpartum period [73].…”
Section: Discussionmentioning
confidence: 99%
“…MacKenzie conducted a study in 203 mothers assessing the correlations of infant sleep quality, parents' sleep, frequency of intercourse and sexual desire up to 12 months after delivery. It was found that poorer infant sleep was associated with poorer partner sleep quality, translating into a lower frequency of intercourse and lower sexual desire [85]. Rowland also showed that insufficient sleep weakened women's libido during the postpartum period [73].…”
Section: Discussionmentioning
confidence: 99%